MODERATING EFFECT OF BOARD INDEPENDENCE ON THE RELATIONSHIP BETWEEN FIRM ATTRIBUTES AND TAX AGGRESSIVENESS: EMPIRICAL EVIDENCE FROM THE NIGERIAN BANKS - Ebire, Kolawole; Musa, Anthony Ahmed; Onmonya, Lucky (International Journal of Accounting & Finance Review, 2024)
Despite increased evidence of the critical role of corporate governance in shaping business behaviour, there is still a lack of understanding of how board independence moderates the relationship between firm qualities and tax aggression, particularly in the context of Nigerian banks. This study examines the moderating effect of board independence on firm attributes and tax aggressiveness relationship in Nigerian banks spanning 2012 to 2022. The firm attribute was proxy as firm size, profitability, leverage, and board independence, while tax aggressive was proxy as the effective tax rate. The data was collected from eleven listed commercial banks in Nigeria. Data analysis were performed using random effects based on the Hausman test. The study concludes that larger banks tend to engage less in tax aggressive strategies than smaller banks. Also, boards with more independent directors tend to be less aggressive in tax activities. In addition, the study concludes that highly leveraged firms have a greater interest in minimising taxes to enhance cash flows available for debt service. Furthermore, when the moderating effect of board independence is introduced, the study concludes that the relationship between profitability and tax aggressiveness was insignificant. Furthermore, larger banks engage in tax aggressiveness when independent directors are involved. More so, the moderating effect of board independent directors will cause a reduction in tax aggressiveness as leverage increases. The study suggest that banks management be encouraged to conduct benchmarking exercises and peer comparisons to assess their tax practices to industry standards. This can help identify outliers and promote a more standardised and responsible approach to tax planning. JEL Classification Codes: M4, M41, M480.